Kiểu nhân vật kỳ ảo - dị biệt trong tiểu thuyết Nguyễn Bình Phương - Trần, Văn Ban (Trường Đại học Đà Lạt, 2012)
Nguyen Binh PHuong created vague, untraditional characters in his works. With miraculous characters, Nguyen Binh PHuong presented Vietnamese's spirit life profamdly and conscicusness that time.